The Effect of Xenophobia on the Public and Political Discourse in the Visegrad Countries : Comparative Analysis of the 2015 & 2022 Refugee Crisis - Roztocil, Klaudia Marie; Votoupalová, Markéta; Barkhatov, Dmitriy; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
In 2015, Europe was facing an unprecedented crisis, when the growing flow of refugees escalated into an uncontrollable influx of people seeking asylum within the borders of the European Union. This crisis revealed the shortcomings and unpreparedness of the European migration policies and caused severe tensions between member states. After less than a decade, Europe was again facing a crisis, however, this time, the source was right by its borders. Since February 2022, Europe has shown extraordinary solidarity towards Ukrainians escaping from the illegal invasion and welcomed the people with open arms. This thesis aims to explore the response of the Visegrad countries to the said crisis and to what extent of the public and political discourse in the region is influenced by xenophobia. Additionally, it aims to assess the relationship between public opinion in comparison to political decisions and policy-making. To reach this set aim, the thesis employs the Intergroup Threat and Securitization theory to establish a theoretical framework. Furthermore, a comparative analysis of these two events will be conducted in order to reach an understanding of this highly complex issue.
Vedoucí práce: Markéta Votoupalová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor bakal. práce]; bakalářské práce; bachelor's theses